Modeling the spatial distribution of Crimean-Congo Hemorrhagic Fever outbreaks in Turkey - Estrada-Pena, Agustin; Vatansever, Zati; Gargili, Aysen; Aktas, Muntr; Uzun, Ramazan; Ergonul, Onder; Jongejan, Frans (Mary Ann Liebert, Inc, 2007)
The more than 1100 human cases of Crimean-Congo Hemorrhagic Fever (CCHF) reported in a continuing series of outbreaks that started in 2003 in Turkey constitute the largest epidemic of the disease since CCHF was first recognized in 1944. The spatial distribution of CCHF case reporting rates in Turkey was studied to look for clusters of disease. We applied the spatial scan analysis to test the hypothesis of whether there were areas with a higher than expected number of CCHF cases. The analysis was conducted through windows of 10, 20, 40 and 80 km in diameter[SR1] to determine whether clustering of cases was dependent on the size of the scanning window. At the largest window size, consistent patterns of significantly higher than expected numbers of CCHF cases were found in a total of 40 administrative districts. A predictive model to map the habitat suitability for the vector tick was developed from satellite-based climate data and high-resolution features of the vegetation from Landsat images covering the whole country. It was found that areas of higher risk (higher CCHF reporting) were correlated (p < 0.05) with zones of high climate suitability for the tick together with a high rate of fragmentation of agricultural land interspersed between forest and shrub-type vegetation.
Keywords: Crimean-Congo Hemorrhagic Fever; Turkey; Hyalomma ticks; spatial model; habitat suitability